2020
DOI: 10.3847/1538-4357/ab8fb1
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons as a Source for (N = 4–6) and C3H2 in the Interstellar Medium

Abstract: Photoionization and dissociation of anthracene, phenanthrene, and pentacene in the multiphoton regime at 266 nm wavelength were performed. (n = 4–6) ions were observed as fragments, and their yields as a function of laser intensity were studied. H-migration and “roaming” mechanisms leading to the formation of these fluxional ions from polycyclic aromatic hydrocarbons (PAHs) are proposed. The present results show higher photostability of PAHs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The photoionization and dissociation of anthracene C 14 H 10 (25.58 Å 3 ), phenanthrene C 14 H 10 (24.28 Å 3 ), and pentacene C 22 H 14 (49.24 Å 3 ) in the multiphoton regime at 266 nm wavelength is well-rationalized in terms of minimum polarizability (the mean polarizabilities calculated with the PBE/Λ22m method are shown in parentheses). Using mass-spectrometry, the authors analyzed the fragmentation ions, formed under irradiation, and found that phenanthrene was more survivable. They concluded about the higher stability of nonlinear PAHs compared to their linear isomers against UV irradiation due to the lower mean polarizability of kinked isomers.…”
Section: Astrochemical Applications Of Polarizabilitymentioning
confidence: 88%
“…The photoionization and dissociation of anthracene C 14 H 10 (25.58 Å 3 ), phenanthrene C 14 H 10 (24.28 Å 3 ), and pentacene C 22 H 14 (49.24 Å 3 ) in the multiphoton regime at 266 nm wavelength is well-rationalized in terms of minimum polarizability (the mean polarizabilities calculated with the PBE/Λ22m method are shown in parentheses). Using mass-spectrometry, the authors analyzed the fragmentation ions, formed under irradiation, and found that phenanthrene was more survivable. They concluded about the higher stability of nonlinear PAHs compared to their linear isomers against UV irradiation due to the lower mean polarizability of kinked isomers.…”
Section: Astrochemical Applications Of Polarizabilitymentioning
confidence: 88%
“…The added proton easily jumps from one carbon atom to another in the molecule and ethylene is only ejected when the proton is bonded to the carbon next to the desorbed C 2 H 4 group. The same hydrogen migration is thought to contribute to H 2 loss (Chen & Luo 2019) and CH + n (n=4-6) fragments (Chacko et al 2020) from PAHs. Further confirmation of ethylene formation is achieved through the IR calculations of the fragment (m/z=181) which are shown in Fig.…”
Section: Confirmation Of the Ethylene Formationmentioning
confidence: 94%
“…The excited PAHs subsequently dissipate their excess energy via several competing channels: ionization, infrared emission, isomerization, and fragmentation (Tielens 2013). PAH fragmentation is believed to play an important role in the catalytic formation of H 2 (Rauls & Hornekaer 2008;Thrower et al 2012), as a source of small hydrocarbons (Chacko et al 2020), and as a part of more complex top-down interstellar chemistry (Zhen et al 2014). It is also an indicator of whether or not PAHs can survive in harsh interstellar environments (Reitsma et al 2014;Gatchell et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…and thus c-C 3 H 2 is mostly destroyed by converting it back to an even larger molecule, c-C 3 H 3 + (Millar et al 1997). The ubiquity of C 2 H and c-C 3 H 2 supports a top-down formation mechanism by release from hydrogenated amorphous carbon, rather than a bottom-up synthesis by gas-phase reaction (Fossé et al 2000;Fuente et al 2003;Teyssier et al 2004;Pety et al 2005;Guzmán et al 2015;Chacko et al 2020) even in dark and diffuse clouds. Recent experimental (Duley et al 2015) and theoretical (Awad & Viti 2022) studies also support this scenario.…”
Section: Other N-bearing Moleculesmentioning
confidence: 99%